ナンキョク リュツォ ホルムワン エンガン ニ サンスル カイソウ ニツイテ - 大野, 正夫; オオノ, マサオ; OHNO, Masao (国立極地研究所, 1976)
P(論文) ラングホブデ,東オングル島,スカルブスネスで海藻調査を行い,その結果ラングホブデでDesmarestia sp.,スカルブスネスでPhyllophora antarctica?の打ち上げ標本を得た.東オングル島では,開氷面よりPhyllophora antarctica A et E.S.GEPPとPhycodrys antarctica(SKOTTSBERG)SKOTTSBERGの2種を採集した.採集地点の生育帯(6-8m)の環境条件は,水温-0.5℃,塩素量17.41-18.25Cl%,水中照度650lxなどであった. This paper is a note on the Antarctic seaweeds collected from the coast of Liitzow-Holm Bay in January 1975. A specimen of Desmarestia sp. (Fig. 1) was found washed ashore on the coast of Langhovde (Lat. 69°14'S, Long. 39°44'E). Antarctic red algae, Phyllophora antarctica A. et E. S. GEPP and Phycodrys antarctica (SKOTTSBERG) SKOTTSBERG (Fig. 2) was collected from beneath the ice on the coast of East Ongul Island (Lat. 69°S, Long. 39°35'E). The water temperature of the habitat was -0.5℃. The light intensity was 650 lx. Phyllophora antarctica A. et E. S. GEPP GEPP and GEPP, 1905, p. 109 1907, p. 15 SKOTTSBERG, 1953, p. 558 NEUSHUL, 1968, pl. 4. Type location : Victoria Land. Distribution : Macrobertson Coast, Adelie Coast, Victoria Land Phycodrys antarctica (SKOTTSBERG) SKOTTSBERG SKOTTSBERG, 1923, p. 35 1953, p. 548 and 562. Type location : Antarctic Peninsula. Distribution : Antarctic Peninsula, Adelie Coast, Macrobertson Coast. departmental bulletin paper